PENGEMBANGAN PERANGKAT PEMBELAJARAN DENGAN PENDEKATAN REALISTIC MATHEMATICS MATERI GEOMETRI PADA MTs BERBASIS KEARIFAN BUDAYA LOKAL SUKU GAYO - Yustinaningrum, Bettri (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2017)
Realistic Mathematics approach based on local wisdom emphasizes the learning of mathematics associated with reality and cultural activities of students. The aim of this study was to: (1) develop learning tools with local wisdom approach Gayo based on realistic mathematics materials Geometry at MTs throughout Central Aceh, (2) promoting the development of the mathematics learning approach to realistic mathematics at MTs throughout Central Aceh through seminars and workshops. Development of the learning device uses 4-D models consist of define, design, development and dissemination. Disseminate phase is the stage of dissemination of devices that have been developed on a wider scale is done through workshops with participants of all teachers of mathematics MTs in Central Aceh. Learning tools created is the syllabus, lesson plans, worksheets, books Student and THB. The results of the learning device test stated that learning tools are valid, effective and practical.Realistic Mathematics approach based on local wisdom emphasizes the learning of mathematics associated with reality and cultural activities of students. The aim of this study was to: (1) develop learning tools with local wisdom approach Gayo based on realistic mathematics materials Geometry at MTs throughout Central Aceh, (2) promoting the development of the mathematics learning approach to realistic mathematics at MTs throughout Central Aceh through seminars and workshops. Development of the learning device uses 4-D models consist of define, design, development and dissemination. Disseminate phase is the stage of dissemination of devices that have been developed on a wider scale is done through workshops with participants of all teachers of mathematics MTs in Central Aceh. Learning tools created is the syllabus, lesson plans, worksheets, books Student and THB. The results of the learning device test stated that learning tools are valid, effective and practical.